Stable Aesthetic Standards Delusion: Changing 'Artistic Quality' by Elaboration. (September 2014) - Carbon, Claus-Christian; Hesslinger, Vera M
The present study challenges the notion that judgments of artistic quality are based on stable aesthetic standards. We propose that such standards are a delusion and that judgments of artistic quality are the combined result of exposure, elaboration, and discourse. We ran two experiments using elaboration tasks based on the repeated evaluation technique in which different versions of the Mona Lisa had to be elaborated deeply. During the initial task either the version known from the Louvre or an alternative version owned by the Prado was elaborated; during the second task both versions were elaborated in a comparative fashion. After both tasks multiple blends of the two versions had to be evaluated concerning several aesthetic key variables. Judgments of artistic quality of the blends were significantly different depending on the initially elaborated version of the Mona Lisa, indicating experience-based aesthetic processing, which contradicts the notion of stable aesthetic standards.